2016
DOI: 10.1007/s00221-016-4848-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) to the supplementary motor area (SMA) influences performance on motor tasks

Abstract: The supplementary motor area (SMA) is believed to be highly involved in the planning and execution of both simple and complex motor tasks. This study aimed to examine the role of the SMA in planning the movements required to complete reaction time, balance, and pegboard tasks using anodal transcranial direct current stimulation (tDCS), which passes a weak electrical current between two electrodes, in order to modulate neuronal activity. Twenty healthy adults were counterbalanced to receive either tDCS (experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…Although there have been few studies observing the metabolic and functional changes following M1-M1 tDCS, the current study is the first to incorporate the SMA as a potential target for bihemispheric tDCS. The SMA has been studied as a potential tDCS target in behavioural studies of posture and visuomotor learning (28, 52). Its anatomical positioning and strong connections to M1 make it a well-suited target for motor network modulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been few studies observing the metabolic and functional changes following M1-M1 tDCS, the current study is the first to incorporate the SMA as a potential target for bihemispheric tDCS. The SMA has been studied as a potential tDCS target in behavioural studies of posture and visuomotor learning (28, 52). Its anatomical positioning and strong connections to M1 make it a well-suited target for motor network modulation.…”
Section: Discussionmentioning
confidence: 99%
“…With its strongest efferent projections to M1 and the corticospinal tract, SMA is a unique target for tDCS (27). Support for this notion comes from a recent study that showed enhanced motor performance by targeting the left SMA with 0.4 mA of anodal tDCS for 90 min over three days (28). By targeting both SMA and M1 with 2mA of tDCS, it may be possible to induce additive effects on M1 excitability via interhemispheric connections, which are thought to be more focal than those associated with M1-supraortibal stimulation (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Areas SMA and pre-SMA are involved in a variety of functions related with motor sequence processing, planning and executing (Hoshi and Tanji 2004; Cona et al 2016; Hupfeld et al 2016), as well as temporal and spatial processing of movements (Mita et al 2009; Kotz and Schwartze 2011). Furthermore, pre-SMA and SMA also contribute to motor learning, speech and language processing (Seitz et al 2006; Kim and Shin 2014; Hertrich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…prior tDCS studies have shown that stimulation of the SMA can increase performance on simple and complex motor tasks [33].…”
Section: Introductionmentioning
confidence: 99%